2008
DOI: 10.1289/ehp.10849
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health and Air Pollution in Asia (PAPA) Project: Estimating the Mortality Effects of Particulate Matter in Bangkok, Thailand

Abstract: BackgroundAir pollution data in Bangkok, Thailand, indicate that levels of particulate matter with aerodynamic diameter ≤10 μm (PM10) are significantly higher than in most cities in North America and Western Europe, where the health effects of PM10 are well documented. However, the pollution mix, seasonality, and demographics are different from those in developed Western countries. It is important, therefore, to determine whether the large metropolitan area of Bangkok is subject to similar effects of PM10.Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 14 publications
2
30
2
Order By: Relevance
“…Where t refers to the day of the observation; E (Yt|X) denotes estimated daily case counts on day t; S () denotes the penalized smoothing spline; 3-8 degrees of freedom (df) per year for time were tested and the df that was chosen had the smallest sum of the absolute partial autocorrelation values over a 30-day lag period ; df*4 denotes the product of 4 (there are 4 years from 2006 to 2009) and df; temperature indicates lag 0-14 average daily mean temperature prior to the death events considering the lagging effects of mean temperature; relative humidity denotes the current day's relative humidity Vichit-Vadakan et al 2008); dow is day of week; holiday is treated as a dummy variable (0 or 1 denote not holiday or holiday) (Morris and Naumova 1998;Roberts 2004).…”
Section: Statistical Methods and Data Analysismentioning
confidence: 99%
“…Where t refers to the day of the observation; E (Yt|X) denotes estimated daily case counts on day t; S () denotes the penalized smoothing spline; 3-8 degrees of freedom (df) per year for time were tested and the df that was chosen had the smallest sum of the absolute partial autocorrelation values over a 30-day lag period ; df*4 denotes the product of 4 (there are 4 years from 2006 to 2009) and df; temperature indicates lag 0-14 average daily mean temperature prior to the death events considering the lagging effects of mean temperature; relative humidity denotes the current day's relative humidity Vichit-Vadakan et al 2008); dow is day of week; holiday is treated as a dummy variable (0 or 1 denote not holiday or holiday) (Morris and Naumova 1998;Roberts 2004).…”
Section: Statistical Methods and Data Analysismentioning
confidence: 99%
“…22 After combining the data of lag0/1 from all the seven cities, the nonaccidental mortality risk significantly increased by 0.24% (95% confidence interval [CI], 0.04 to 0.45), and the cardiovascular mortality risk significantly increased by 0.29% (95% CI, 0.09 to 0.5) for every 10-mg/m 3 increase in PM 10 concentration.…”
Section: Pm 10 Thresholds For Daily Cause-specific Mortalitiesmentioning
confidence: 99%
“…Furthermore, exposure to higher concentrations of fine particulate matter which contains inorganic elements can have deleterious health impacts on living organisms [4]. Short-and long-term exposure to particulate matter are related to mortality, hospital admission, decreased lung function and related health symptoms [5]; a study by Vichit-Vadakan et al [6] reported a statistical significance between daily mortality and concentrations of PM 10 . PM 10 or particulate matter < 10 μm can penetrate the trachea and lower aerodynamic diameter fractions can even reach the alveoli [7].…”
Section: Introductionmentioning
confidence: 99%